New Paths to Online Teaching - How Can We Manage Knowledge Transfer and Make the Learning More Enjoyable? - András Benedek (Debrecen University Press, 2021)
This study is based on the results from a national project initiative on digitalization, supported by methodology evidence from e-learning materials at the level of teachers' training for vocational education institutes. Looking for the new paths to online learning We have been formulating the question for almost a decade: How can we manage the transfer of knowledge and make learning more enjoyable? For the steps forwards, the first impulses for understanding the recontextualization of vocational didactics and re-defining roles and responsibilities of the actors. Our paper deals with seeking a new method for content development and its application in vocational education and training (VET). This study recommends a kind of open framework[1] is provided by the fact that the innovation, which takes open source content development as one of the approaches of reforming teacher training for VET, is connected to a technical university of long-existing traditions. In line with the peculiarities of Hungarian VET, our research group undertook to develop methodological training in terms of complex school subjects. By applying their new concept, their concrete objective was: the methodological renewal of vocational teacher training and practical training by creating and applying complex learning content units online.